2020
DOI: 10.1111/os.12711
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery Oblique Lumbar Interbody Debridement and Fusion for the Treatment of Lumbar Spondylodiscitis

Abstract: Objective To evaluate the efficacy and feasibility of minimally invasive oblique lumbar interbody debridement and fusion for the treatment of conservatively ineffective lumbar spondylodiscitis. Methods This is a retrospective study. Between December 2016 and November 2017, a total of 14 consecutive patients (eight males and six females, with an average age of 49.1 years, range from 42 to 74 years) with single‐level lumbar spondylodiscitis were included in the study. The inclusion criteria include single‐level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Recently, multiple retrospective studies have reported greater improvement in sagittal alignment with instrumentations [72]. TLIF technique may be the best familiar pathway to achieve complete debridement, access the disc space, remove an avascular disc, achieve circumferential fusion, and avoid the unfamiliar anterior approach [21,23,[73][74][75][76]. In our series of 19 patients, we achieved reasonable mean operative time, EBL, less LOH, fewer complication rates, and quick improved back pain VAS (Tables 3, 4).…”
Section: Discussionmentioning
confidence: 60%
“…Recently, multiple retrospective studies have reported greater improvement in sagittal alignment with instrumentations [72]. TLIF technique may be the best familiar pathway to achieve complete debridement, access the disc space, remove an avascular disc, achieve circumferential fusion, and avoid the unfamiliar anterior approach [21,23,[73][74][75][76]. In our series of 19 patients, we achieved reasonable mean operative time, EBL, less LOH, fewer complication rates, and quick improved back pain VAS (Tables 3, 4).…”
Section: Discussionmentioning
confidence: 60%
“…In conclusion, we would like to note the versatility of this method of fusion: it can be used for a wide range of degenerative diseases of the lumbar spine, deformities, traumatic injuries, infections, and tumor lesions [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The late complications such as fusion cage displacement and sink and breakage of internal fixation were detected. VAS is one of the most commonly used index to measure the degree of pain 27 and ODI is a condition‐specific outcome measure for spinal disorders. 28 …”
Section: Methodsmentioning
confidence: 99%